PERBANDINGAN RADIOGRAFI Os MANDIBULAR BODY POSTERO-ANTERIOR TEGAK LURUS DENGAN POSTERO-ANTERIOR AXIAL 30* CHEPALAD: Radiographic Comparison of Perpendicular Postero-Anterior Os Mandibular and Cephalad Postero-Anterior Axial of 30* Chepalad - Cicillia Artitin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2020)
Os.mandibular body is a lower jaw bone that serves as a place for attaching teeth and shaped like a horseshoe. Based on observations at the hospital during observation at the Central Hospital, DR. M. Djamil Padang has no special examination to show the Os.mandibular body, even though the technique of examining the projection of the Postero-Anterior projection is perpendicular to the Postero-Anterior axial 300chepalad, the mandibular ramus and condyles are more visible. The study aimed to find out the optimal description of the Osiband body by comparing the Postero-Anterior projection perpendicular to the Postero-Anterior axial 300chepalad of the mandibular ramus and the more visible condyles. The type of research used in this study is a type of quantitative research with an experimental study conducted at the Radiology Installation of the Central Hospital DR. M. Djamil Padang on the March - April 2019 by using a sample of 3 patients, then read by 5 respondents and processing data using a table. The results of this study indicate that the average value of perpendicular Postero-Anterior projection is 1.28 because it can display the anatomy of the os.mandibular body looking quite optimal, the image of the mandibular ramus looks quite symmetrical, but it is less able to display the condyles and Mandibular symphysis is good and clear compared to the Postero-Anterior axial 300 chepalad projection with an average value of 1.84 because it is better able to show a clear picture of the condyles and mandibular symphysis looks better and clearer.